Religiosity and spirituality in mental health: nurses’ training, knowledge and practices - Silva Filho,José Adelmo da (2022)
ABSTRACT Objective: to analyze nurses’ training, knowledge and practices in the religiosity/spirituality interface in the context of Psychosocial Care Centers. Methods: a descriptive, exploratory, qualitative study, carried out in a metropolitan region of Ceará. Four nurses were interviewed, and the data were examined using the content analysis technique. Results: four categories emerged from analysis: Deficit in teaching religious and spiritual practices in higher education in nursing; View of the concept of religiosity and spirituality; Religiousness and spirituality as an integral part of the person; Reception of religious and spiritual practices as an aid to treatment. Final considerations: a deficit in nursing undergraduate teaching was identified concerning religiosity and spirituality. However, the interviewed professionals understand the importance of religious and spiritual dimensions in the therapeutic process, even though they do not accurately differentiate the concepts.